2014
DOI: 10.3732/apps.1400034
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fungus‐specific microsatellite markers in the lichen fungus Usnea subfloridana (Parmeliaceae)

Abstract: • Premise of the study: Microsatellite loci were developed for the haploid lichenized fungal species Usnea subfloridana to study its population subdivision and the species’ response to forest disturbance, fragmentation, and environmental pollution.• Methods and Results: We developed 14 polymorphic microsatellite markers using 454 pyrosequencing data of U. subfloridana. The number of alleles per locus ranged from three to 15, and Nei’s unbiased gene diversity averaged over nine markers without null alleles rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Particularly, the largest florida-subfloridana clade was reminiscent of the situation in another species pair, Usnea antarctica vs. U. aurantiacoatra, in which microsatellite markers and a RADseq approach demonstrated that the sexual and asexual morphs largely formed separate taxa (Lagostina et al 2018;Grewe et al 2018). Tõrra et al (2014) and Degtjarenko et al (2018Degtjarenko et al ( , 2019 developed microsatellite markers for the U. subfloridana complex, but did not report on their potential use to separate U. florida from U. subfloridana.…”
Section: Usnea Subgenus Neuropogon New Zealand Cladementioning
confidence: 98%
“…Particularly, the largest florida-subfloridana clade was reminiscent of the situation in another species pair, Usnea antarctica vs. U. aurantiacoatra, in which microsatellite markers and a RADseq approach demonstrated that the sexual and asexual morphs largely formed separate taxa (Lagostina et al 2018;Grewe et al 2018). Tõrra et al (2014) and Degtjarenko et al (2018Degtjarenko et al ( , 2019 developed microsatellite markers for the U. subfloridana complex, but did not report on their potential use to separate U. florida from U. subfloridana.…”
Section: Usnea Subgenus Neuropogon New Zealand Cladementioning
confidence: 98%
“…The maximum number of alleles of the most variable marker found in the 264 specimens analyzed was five. This is considerably lower than the 11 alleles found in Lobaria pindarensis (Devkota et al 2014), 13 in both Nephroma laevigatum (Belinchón et al 2014) and Bryoria section Implexae (Nadyeina et al 2014a), 15 in Usnea subfloridana (Tõrra et al 2014) and 16 in Lobaria pulmonaria (Walser et al 2003;Werth et al 2013). However, the values are comparable to the three alleles found in Parmotrema tinctorum (Mansournia et al 2012), six in both Nephroma parile (Belinchón et al 2014) and Protoparmeliopsis muralis (Guzow-Krzemińska & Stocker-Wörgötter 2013) and eight in Lobarina scrobiculata (Prieto et al 2015).…”
Section: Specificity and Polymorphism Of The New Microsatellite Markersmentioning
confidence: 74%
“…2014) and Bryoria section Implexae (Nadyeina et al 2014 a ), 15 in Usnea subfloridana (Tõrra et al . 2014) and 16 in Lobaria pulmonaria (Walser et al . 2003; Werth et al .…”
Section: Discussionmentioning
confidence: 99%
“…The total genomic DNA was extracted using PowerPlant Pro DNA Isolation Kit and DNeasy Plant Mini Kit (MO BIO Laboratories, Inc., Qiagen, USA), according to the manufacturer’s protocol. Seven fungal microsatellite loci ( Us02 , Us03 , Us04 , Us05 , Us06 , Us08 and Us09 ) were amplified in two multiplex PCR using QIAGEN Multiplex PCR Kit, following the instructions described in Tõrra et al (2014) and Degtjarenko et al (2016). Fragment lengths of PCR products were determined on a 3730xl DNA Analyzer (Applied Biosystems) with LIZ-500 as the internal size standard.…”
Section: Methodsmentioning
confidence: 99%